A Review on Sensor‐Integrating Machine Elements - Eckhard Kirchner; Thomas Wallmersperger; Thomas Gwosch; Johannes D. M. Menning; Julian Peters; Richard Breimann; Benjamin Kraus; Peter Welzbacher; Jan Küchenhof; Dieter Krause; Erich Knoll; Michael Otto; et al. (Advanced Sensor Research, 2024)
Abstract This contribution summarizes the current state of research regarding so‐called sensor‐integrating machine elements as an enabler of digitalization in mechanical engineering and——if available—their application in industry. The focus is on the methodical aspects of the development of these machine elements in general as well as specific sensor‐integrating machine elements that are either already in use or currently under development. Developmental aspects include the robust design of initially evaluated concepts for sensor‐integrating machine elements as well as their modularization. Smart materials with sensory functions are included in the analysis as well as the differentiation with regard to add‐on sensors. The aim of the authors interlinked by a special research program funded by the German Research Foundation (DFG) is to facilitate the exchange with other researchers with the help of the comprehensive overview given in this contribution. The contribution concludes with a brief discussion of open challenges, such as the energy supply and data transfer in rotating systems and also data security.